Design of a Microstrip Diplexer and Triplexer Using Open Loop Resonators - Chinig,A. (2016)
Abstract In this paper a novel design of microstrip diplexer and triplexer using open loop resonators is presented. The proposed diplexer if formed by two band-pass filters for the Industrial Scientific Medical (ISM) applications at 5.8 GHz and the WIMAX applications (IEEE 802.16 WiMAX at 3.17 GHz to 4.2 GHz bands). The microstrip triplexer is designed for the Digital Communication System (DCS) at 1.8 GHz, WIMAX at 3.2 GHz and for the C-band at 4.4 GHz. Each device is formed by a set of filters with a matching network by using open loop resonators and a good arrangement of the transmission feed lines. Several parametric studies were achieved to study the influence of some critical parameters on the performances of the proposed circuits. The LC equivalent circuit of the band pass filter is examined and the values of its components are calculated. ADS Agilent and CST-MWS solvers are used to predict the electrical performances of the proposed circuits. The simulated frequency responses of these structures show good results with insertion losses around 2 dB, return losses better than 20 dB for all channels, and an isolation between all bands better than 20 dB. Besides, several transmission zeros are observed near the pass bands which enhance the selectivity and the isolation of the proposed devices.